PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN VERSTEK JUAL BELI HAK ATAS TANAH PROGRAM TRANSMIGRASI (STUDI PERKARA NOMOR 28/PDT.G/2020/PN.BKN) - Effendi, Devirianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Law Number 5 of 1960 and Government Regulation Number 24 of 1997 concerning Land Registration, for legal certainty the transfer (sale and purchase) must be made in front of the PPAT and registered at the local land agency office. Based on decision Number 28/Pdt.G/2020/PN.Bkn in Tanah Datar Village, Kampar Regency, there has been a sale and purchase of land that was only carried out by the parties in front of the Village Head, where this would make it difficult for the parties regarding legal certainty, and what it is feared that this will happen to the buyer where he will experience difficulties when registering the land to obtain the certificate. The plaintiff filed a suit with the court for this purpose. This lawsuit was terminated by a verstek decision because the defendant's domicile was no longer known. The problems discussed in this thesis are first, what are the judges' considerations in passing the verstek decision in case Number 28/Pdt.G/2020/PN.Bkn? Second, what are the legal consequences for the disputing parties (plaintiff and defendant) in case Number 28/Pdt.G/2020/PN.Bkn? Based on the results of the research and discussion obtained first, the judge's consideration in deciding the case of buying and selling land rights for the transmigration program based on decision Number 28/Pdt.G/2020/PN.Bkn, has been right in passing the verstek decision because it has fulfilled the requirements specified in the procedural law and is in accordance with the provisions of Article 125 HIR (Herzien Inlandsch Reglement). Second, the legal consequence of the decision Number 28/Pdt.G/2020/PN.Bkn against the parties is that the plaintiff and the defendant must comply with the judge's decision because the judge wins the plaintiff's party, so the case costs are charged to the defendant and the land and object of the case remain on the side plaintiff.